Regeneration of activated carbon by combined ultrasound and persulfate treatment - Shiwei Gao; Zheng Wang; Yannan Jia; Nannan Xu; Lisha Liao; Zhiwei Wang; Binbin Wu; Wanting Feng; Yuanxiang Shan; Lingpeng Hu; Hongqin Xue (Arabian Journal of Chemistry, 2024)
In this study, the regeneration of waste activated carbon by the synergic combination of ultrasonication and persulfate treatment was explored. The regeneration efficiencies achieved with sonication and persulfate, both in combination and separately, were assessed from a sample’s ability to adsorb ofloxacin before and after regeneration. The introduction of persulfate increased the regeneration rate by 4–5% over that of ultrasound alone, and the regeneration rate increased from 40.95 % to 45.71 % upon increasing the persulfate dosage from 1 to 10 mmol/L. Furthermore, the regeneration rate was found to be largely unaffected by pH. The specific surface area of the activated carbon regenerated by the combined technology was 527 m2/g, which was 37 m2/g higher than that for ultrasonic regeneration alone, further demonstrating the utility of the combined approach. In summary, combined ultrasonication/persulfate regeneration provides a practical and cost-effective method for the reuse of waste activated carbon.